Synthesis, characterization and catalytic properties of hexagonal mesoporous vanadium aluminophosphate molecular sieves - Venkatathri, N; Srivastava, R (Catalysis Communications, 2005)
Novel vanadium containing hexagonal mesoporous aluminophosphate molecular sieve (VHMA) have been synthesized. XRD and TEM analysis confirm the phase purity of the synthesized samples. FT-IR analysis suggests the incorporation of V4+ in the aluminophosphate framework. ESR, UV-Vis spectroscopic techniques and cyclic voltammetric studies confirm the incorporation of vanadium and reveal its presence of tetrahedral and square pyramidal environments in the as-synthesized samples. Cyclic voltammetry reveals the presence of two redox couples in VHMA. This catalyst is found to be a good oxidation catalyst. (C) 2005 Elsevier B.V. All rights reserved.